Summer solstice orchestrates the subcontinental-scale synchrony of mast seeding - Journé, Valentin; Szymkowiak, Jakub; Foest, Jessie; Hacket-Pain, Andrew; Kelly, Dave; Bogdziewicz, Michał (My University, 2023)
High interannual variation in seed production in perennial plants can be synchronized at subcontinental scales with wide consequences for ecosystem functioning, but how such synchrony is generated is unclear. We investigated the factors contributing to masting synchrony in European beech, spanning an impressive 2000 km geographic range. Maximizing masting synchrony via spatial weather coordination, known as the Moran effect, requires distant populations to react simultaneously to weather conditions. A celestial cue that occurs simultaneously across the entire Hemisphere is the longest day (summer solstice). We show that European beech abruptly opens its temperature-sensing window on the solstice, hence widely separated populations all start responding to weather signals in the same week. This celestial "starting gun" generates ecological events with unparalleled spatial synchrony across the continent.
To jest autorska wersja manuskryptu (AAM) artykułu opublikowanego w czasopiśmie "Nature Plants"
Keywords: mast seeding; photoperiod; phenology; day length; regional synchrony; seed production